Functional expression of the thyrotropin receptor in C cells: new insights into their involvement in the hypothalamic-pituitary-thyroid axis - Morillo-Bernal, Jesús (Blackwell Science Inc, 2009)
Thyroid C cells, or parafollicular cells, are mainly known for producing calcitonin, a hormone involved in calcium homeostasis with hypocalcemic and hypophosphatemic effects. Classically, the main endocrine activity of this cell population has been believed to be restricted to its roles in serum calcium and bone metabolism. Nonetheless, in the last few years evidence has been accumulating in the literature with regard to local regulatory peptides secreted by C cells, such as somatostatin, ghrelin, thyrotropin releasing hormone or the recently described cocaine- and amphetamine-related transcript, which could modify thyroid function. As thyrotropin is the main hormone controlling the hypothalamic-pituitary-thyroid axis and, accordingly, thyroid function, we have examined the functional expression of the thyrotropin receptor in C-cell lines and in thyroid tissues. We have found that rat and human C-cell lines express the thyrotropin receptor at both mRNA and protein levels. Furthermore, incubation of C cells with thyrotropin resulted in a 10-fold inhibition of thyrotropin-receptor expression, and a concomitant decrease of the steady-state mRNA levels for calcitonin and calcitonin gene-related peptide determined by quantitative real-time PCR was found. Finally, thyrotropin receptor expression by C cells was confirmed at protein level in both normal and pathological thyroid tissues by immunohistochemistry and immunofluorescence. These results confirm that C cells, under regulation by thyrotropin, are involved in the hypothalamic-pituitary-thyroid axis and suggest a putative role in local fine-tuning of follicular cell activity.